DEGRADATION OF POLYETHYLENE PLASTIC WASTE BY INDIGENOUS MICROBIAL CONSORTIUM AND FUNGI - Melati Ferianita Fachrul; Astri Rinanti; Tazkiaturrizki Tazkiaturrizki; Salmiati Salmiati; Thalia Sunaryo (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2021)
Aim: The aims of this research is to determine the ability of an indigenous microbial consortium to degrade Low Density Polyethylene plastics. The plastic was cut mechanically into 1 x 1 cm2 pieces because the smaller the size of the plastic, the larger the surface area. The samples are input in an Erlenmeyer flask containing indigenous microbial consortium and fungi (20% v/v) and Stone Mineral Salt solution media (80% v/v). This research lasted 10 days with a pH of 7 controlled and temperature variations of 25, 30, 35°C. As preliminary research, the sensitivity test seeks to demonstrate that the indigenous microbial consortium and fungi are resistant or insensitive to LDPE. The degradation of LDPE plastic was analyzed using gravimetric methods, Fourier Transform Infrared, and a scanning electron microscope. Methodology and results: According to the results of gravimetric and FTIR analysis, the highest removal value was at a temperature variation of 30°C. The gravimetric analysis revealed that the weight loss in LDPE plastic was 0.0082 gr to 0,0074 gr or 9.76 %, while the FTIR analysis revealed that the intensity removal result was 6,27 %. Conclusion, significance, and impact of study: Scanning Electron Microscope (SEM) analysis revealed morphological changes on the surface of LDPE plastic samples, confirming these findings. Several factors influence the changes that occur in this study's LDPE plastic samples.